Membrane depolarization and aberrant lipid distributions in the neonatal rat brain following hypoxic-ischaemic insult - Luptakova, Dominika; Baciak, Ladislav; Pluhacek, Tomas; Skriba, Anton; Sediva, Blanka; Havlicek, Vladimir; Juranek, Ivo (Scientific reports, 2018)
Neonatal hypoxic-ischaemic (HI) encephalopathy is among the most serious complications in neonatology. In the present study, we studied the immediate (0 hour), subacute (36 hours) and late (144 hours) responses of the neonatal brain to experimental HI insult in laboratory rats. At the striatal level, the mass spectrometry imaging revealed an aberrant plasma membrane distribution of Na+/K+ ions in the oedema-affected areas. The failure of the Na+/K+ gradients was also apparent in the magnetic resonance imaging measurements, demonstrating intracellular water accumulation during the acute phase of the HI insult. During the subacute phase, compared with the control brains, an incipient accumulation of an array of N-acylphosphatidylethanolamine (NAPE) molecules was detected in the HI-affected brains, and both the cytotoxic and vasogenic types of oedema were detected. In the severely affected brain areas, abnormal distributions of the monosialogangliosides GM2 and GM3 were observed in two-thirds of the animals exposed to the insult. During the late stage, a partial restoration of the brain tissue was observed in most rats in both the in vivo and ex vivo studies. These specific molecular changes may be further utilized in neonatology practice in proposing and testing novel therapeutic strategies for the treatment of neonatal HI encephalopathy.
Keywords: membránové potenciály; Rats; lipidy; Animals, Newborn; Cell Membrane; Rats, Wistar; mužské pohlaví; Hypoxia-Ischemia, Brain; mozek; novorozená zvířata; Membrane Potentials; krysa rodu Rattus; Lipids; Brain; ženské pohlaví; zvířata; mozková hypoxie a ischemie; Acute Disease; buněčná membrána; potkani Wistar; akutní nemoc; Female; Male; Animals